La producción y difusión del conocimiento. El caso del Boletín del Instituto Psicopedagógico Nacional (1942-1953 - De la Vega Ramírez, Aurora (2013)
The study of a scientific journal allows knowing the process of creation and dissemination of knowledge, as well as the interests and trends of a given era. The article presents the case of the Bulletin of the National Psychopedagogical Institute that was published between 1942 and 1953, and which spread the activities of the institution, the research about Peruvian school students and the educational reality of that time. However the quality of published work, thanks to the effort of a remarkable group of researchers with European education, the Bulletin stopped appearing as a result of the deactivation of the Institute, fact that was celebrated by some educators. The article reflects on the state of scientific research in Peru whose conditions, then and now, limit the production and application of knowledge generated by the research activity